2016
DOI: 10.1681/asn.2015060664
|View full text |Cite
|
Sign up to set email alerts
|

Urine of Preterm Neonates as a Novel Source of Kidney Progenitor Cells

Abstract: In humans, nephrogenesis is completed prenatally, with nephrons formed until 34 weeks of gestational age. We hypothesized that urine of preterm neonates born before the completion of nephrogenesis is a noninvasive source of highly potent stem/progenitor cells. To test this hypothesis, we collected freshly voided urine at day 1 after birth from neonates born at 31-36 weeks of gestational age and characterized isolated cells using a single-cell RT-PCR strategy for gene expression analysis and flow cytometry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 47 publications
6
44
0
Order By: Relevance
“…Remarkably, we confirmed the presence of FODX1 + cells in the CM SIX2 + CITED1 + cells (Fig. 5B) . It is important to note that the isolation method for these cells differs from the Smartflare technique used in the current work.…”
Section: Resultssupporting
confidence: 74%
“…Remarkably, we confirmed the presence of FODX1 + cells in the CM SIX2 + CITED1 + cells (Fig. 5B) . It is important to note that the isolation method for these cells differs from the Smartflare technique used in the current work.…”
Section: Resultssupporting
confidence: 74%
“…UdRPCs express key renal progenitor-regulatory proteins SIX2, CITED1, WT1 and NPHS1 ( Figure 2A) indicating they originate from the kidney as described from others. 13,56,60 Furthermore, UdRPCs transport Albumin ( Figure 2B) as observed in renal stem cells. 41,61 We have shown that UdRPCs are in fact bon-fide MSCs-i.e.…”
Section: Discussionmentioning
confidence: 66%
“…Here we describe urine as a reliable, robust and cheap source of renal stem cells, in contrast to amniotic fluid or kidney biopsies. 41,56 Urine can be accessed non-invasively, without risk for the patient and repeated samples can be collected from the same donor over prolonged periods. Urine derived stem cells can be expand from a single clone with high proliferation potency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generating renal cells using human stem cells offers a promising approach to study podocytopathies. Amniotic fluid stem cells as well as kidney progenitor cells from neonatal urine have the potential to differentiate towards podocyte-like cells, though these sources are relatively scarce [54]. The recent progress of reprogramming any somatic cell type (e.g., human dermal fibroblasts) into pluripotent stem cells has opened a new dimension to develop, in principal, any desired cell type, including renal tissue.…”
Section: Modeling Ns Using Stem Cellsmentioning
confidence: 99%